Beating the odds: Confrontational deliberative democracy (2014)
Even the most skeptical views might concede that deliberative practices, if ever realized, have the potential to provide contemporary democracies, including those in divided societies, with a much needed, reinvig-orating boost. But achievement of a minimal consensus on conditions for that realization, and their feasibility, nevertheless lies way ahead. In the search for elements of discussion that might help us advance in this debate, the cross-sectional assessment given here, based on the various cases presented throughout the book, suggests how aspects of confrontation and deliberation could be regularly combined in practice, and what general conditions could facilitate such an uneasy accommodation.